Impact of Age on Atrial Fibrillation Recurrence Following Surgical Ablation - MacGregor, Robert M. (J Thorac Cardiovasc Surg, 2020)
OBJECTIVES: The incidence of atrial fibrillation (AF) in patients over 75-years of age is expected to increase, and it’s treatment remains challenging. This study evaluated the impact of age on the outcomes of surgical ablation (SA) of AF. METHODS: A retrospective review was performed of patients who underwent the Cox-Maze IV procedure (CMP-IV) at a single institution between 2005 and 2017. The patients were divided into a younger (age<75,n=548) and an elderly cohort (age≥75,n=148). Rhythm outcomes were assessed at 1 year and annually thereafter. Predictors of first atrial tachyarrhythmias (ATAs) recurrence were determined using Fine-Gray regression, allowing for death as the competing risk. RESULTS: The mean age of the elderly group was 78.5 ± 2.8 years. The majority of patients (423/696, 61%) had non-paroxysmal AF. The elderly patients had a lower BMI (P<0.001) and higher rates of hypertension (P=0.011), previous myocardial infarction (P=0.017), heart failure (P<0.001), and preoperative pacemaker (P=0.008).Postoperatively, the elderly group had a higher rate of overall major complications (23%vs14%, P=0.017) and 30-day mortality (6%vs2%, P=0.026). The percent freedom from ATAs and antiarrhythmic drugs (AADs) was lower in the elderly patients at 3 (69%vs82%, P=0.030) and 4 years (65%vs79%, P=0.043). By competing risk analysis, the incidence of first ATAs recurrence was higher in elderly patients (33%vs20% at 5 years; Gray’s test, P=0.005). On Fine-Gray regression adjusted for clinically relevant covariates, increasing age was identified as a predictor of ATAs recurrence ((SHR) 1.03, 95% CI (1.02,1.05), P<0.001). CONCLUSIONS: The efficacy of the CMP-IV was worse in elderly patients, however the majority of patients remained free of ATAs at 5 years. The lower success rate in these higher risk patients should be considered when deciding to perform SA.